Immersion with menthol improves recovery between 2 cycling exercises in hot and humid environment - Rinaldi, K.; Trong, T. T.; Riera, F.; Appel, K.; Hue, O. (Applied Physiology, Nutrition, and Metabolism, 2018)
Endurance exercise performance is impaired in a hot and humid environment. This study compared the effects of cold water immersion, with (CMWI) and without (CWI) menthol, on the recovery of cycling performance. Eight heat-acclimatized cyclists (age, 24.1 ± 4.4 years; mass, 65.3 ± 5.2 kg) performed 2 randomized sessions, each consisting of a 20-min cycling trial (T1) followed by 10 min of immersion during recovery and then a second 20-min cycling trial (T2). Mean power output and perceived exertion (RPE) were recorded for both trials. Rectal (Trec) and skin temperatures were measured before and immediately after T1, immersion, and T2. Perceived thermal sensation (TS) and comfort were measured immediately after T1 and T2. Power output was significantly improved in T2 compared with T1 in the CMWI condition (+15.6%). Performance did not change in the CWI condition. After immersion, Trec was lower in CWI (-1.17 °C) than in CMWI (-0.6 °C). TS decreased significantly after immersion in both conditions. This decline was significantly more pronounced in CMWI (5.9 ± 1 to 3.6 ± 0.5) than in CWI (5.6 ± 0.9 to 4.4 ± 1.2). In CMWI, RPE was significantly higher in T1 (6.57 ± 0.9) than in T2 (5.14 ± 1.25). However, there was no difference in TC. This study suggests that menthol immersion probably (i) improves the performance of a repeated 20-min cycling bout, (ii) decreases TS, and (iii) impairs thermoregulation processes.